They may not mean to, but they do [large type] - Schine, Cathleen (Thorndike Press, Gale Cengage Learning, 2016)
Joy Bergman is not slipping into old age with the quiet grace her children, Molly and Daniel, would prefer. She won't take their advice, and she won't take an antidepressant. The Bergman clan has always stuck together, growing as it incorporated in-laws, ex-in-laws, and same-sex spouses. When Joy's husband Aaron dies, Molly and Daniel have no shortage of solutions for their mother's loneliness and despair, but there is one challenge they did not count on: the reappearance of an ardent suitor from Joy's college days.